PENGARUH DISIPLIN KERJA, PRESTASI KERJA DAN LOYALITAS KERJA TERHADAP PROMOSI JABATAN KARYAWAN PADA PT. ASTRA INTERNATIONAL Tbk-CABANG SISINGAMANGARAJA MEDAN - Dannu Bagus Utama; Cahyo Pramono; Suwarno Suwarno (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The study aims to examine and analyze the effect of work discipline, work performance and work loyalty on promotion of production employees at PT. Astra International Tbk-Cabang SM Raja Medan. The population in this study were all employees of the production section of PT. Astra International Tbk-Cabang SM raja Medan totaling 50 employees. This type of research uses explanatory research whit a quantitative approach. The sample technique used in this study uses saturated sampling. The data collection technique in this research is a questionnaire / questionnaire. Methods of data analysis using descriptive analysis, multiple linear regression analysis and partial determination coefficient. Data analysis was performed using statistics whit SPSS version 21. The results of regression analysis of work discipline have a negative effect on promotion, with a regression coefficient of -1.446 which means that a decrease in work discipline will be followed by a decrease in opportunities for promotion. Job performance has a positive effect on promotion, with a regression coefficient of 1.028, which means an increase in work performance will be followed by an increase in promotion. Job loyalty has a negative effect on promotion, with a regression coefficient of -0.025, which means that a decrease in job loyalty will be followed by a decrease in promotion. The results of the F test show that work discipline, work performance and loyalty simultaneously have a positive and significant effect on promotion.Keywords: Work Discipline, work Performance, work Loyalty and work Promotion